Spontaneous pneumothorax during nintedanib therapy in patients with systemic sclerosis‐associated interstitial lung disease. Issue 3 (27th January 2021) - Sumi, Toshiyuki; Uehara, Hirofumi; Tada, Makoto; Keira, Yoshiko; Kamada, Koki; Shijubou, Naoki; Yamada, Yuichi; Nakata, Hisashi; Mori, Yuji; Chiba, Hirofumi
Abstract: Interstitial lung disease (ILD) is a common complication of systemic sclerosis (SSc). Nintedanib, an antifibrotic drug, has recently been approved for treating SSc‐ILD. Although there have been no reports suggesting the development of pneumothorax with nintedanib use, its safety in patients with impaired lung function is unclear. We observed the development of refractory spontaneous pneumothorax during nintedanib therapy in two patients with SSc‐ILD and impaired lung function. Nintedanib use for SSc‐ILD, an extensive disease, may therefore increase the risk of pneumothorax. In addition, pneumothorax is more likely to be refractory in these cases; initiation of nintedanib treatment and follow‐up should be considered carefully. Abstract : We observed the development of refractory spontaneous pneumothorax during nintedanib therapy in two patients with systemic sclerosis and interstitial lung disease (SSc‐ILD) and impaired lung function. Nintedanib use for SSc‐ILD, an extensive disease, may therefore increase the risk of pneumothorax. In addition, pneumothorax is more likely to be refractory in these cases; initiation of nintedanib treatment and follow‐up should be considered carefully.